Does the Polycentric Urban Region Contribute to Economic Performance? The Case of Korea - Kyusang Kwon (Sustainability, 2018)
This study aims to explore whether and to what extent two types of polycentricity, morphological and functional, affect the level of urban economic performance. In the analysis, it is found that morphological polycentricity is positively associated with the level of labor productivity whereas functional polycentricity is negatively related to it. In the context of the Korean urban system, characterized by the domination of a few cities and high levels of population density, regions which are more morphologically polycentric and functionally monocentric are likely to have higher labor productivity. These results reflect the processes of agglomeration economies and their impact on urban dynamics. This study contributes to the debates on the impacts of polycentricity on economic performance by examining this relationship in the East Asian context, not in Europe or America, and by distinguishing between effects of two types of polycentricity.